2008
DOI: 10.1016/j.anbehav.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The information banded mongooses extract from heterospecific alarms

Abstract: The information banded mongooses extract from heterospecific alarms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…First, they emphasize that individuals are selected to exploit any available information sources when making risk-sensitive decisions, whether incidental features of companions and the environment (Blumstein et al 2004;Monclus et al 2005), or actively broadcast signals, either conspecific (Manser et al 2002) or heterospecific (Rainey et al 2004;Magrath et al 2007;Muller & Manser 2008). Second, they highlight an important reinterpretation of vigilance in social groups: increased vigilance by companions, rather than allowing a relaxation of personal vigilance (Pulliam 1973;Bahr & Bekoff 1999), instead may often indicate that risk has increased, which should select for increased personal vigilance (Sirot 2006;Beauchamp 2008).…”
Section: Discussionmentioning
confidence: 99%
“…First, they emphasize that individuals are selected to exploit any available information sources when making risk-sensitive decisions, whether incidental features of companions and the environment (Blumstein et al 2004;Monclus et al 2005), or actively broadcast signals, either conspecific (Manser et al 2002) or heterospecific (Rainey et al 2004;Magrath et al 2007;Muller & Manser 2008). Second, they highlight an important reinterpretation of vigilance in social groups: increased vigilance by companions, rather than allowing a relaxation of personal vigilance (Pulliam 1973;Bahr & Bekoff 1999), instead may often indicate that risk has increased, which should select for increased personal vigilance (Sirot 2006;Beauchamp 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Müller and Manser (2008) reported that banded mongooses Mungos mungo responded to alarm calls of three plover Vanellus species suggesting that banded mongooses use heterospecific alarms for predator avoidance but do not use additional information provided in these signals (high vs. low urgency). Vitousek et al (2007) found even a response of a non-vocal reptile to the alarm calls of a bird.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, young vervet monkeys, Cercopithecus aethiops, acquire the ability to respond to the alarm calls of starlings as they age, and do so more quickly when exposed to more starling alarms, suggesting learning (Hauser 1988). Learning rather than similarity is likely to be important in species responding to heterospecific alarm calls that differ from their own, such as among birds (Hurd 1996;Templeton & Greene 2007), among mammals (Shriner 1998;Zuberbü hler 2000;Fichtel 2004) and when birds respond to mammal alarms (Rainey et al 2004) or mammals respond to bird alarms (Mü ller & Manser 2008).…”
Section: Introductionmentioning
confidence: 99%